2012
DOI: 10.3111/13696998.2012.673525
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of dabigatran etexilate for stroke prevention in non-valvular atrial fibrillation. Applying RE-LY to clinical practice in Denmark

Abstract: Based on the outcomes observed in the RE-LY trial, dabigatran represents a cost-effective alternative to warfarin in Denmark for all patients with atrial fibrillation within the licensed indication of dabigatran.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 22 publications
2
28
0
1
Order By: Relevance
“…In fact, in several studies, dabigatran etexilate was found to be cost effective among different countries and settings [61,[66][67][68][69]. Similarly, two analyses recently established the cost effectiveness of rivaroxaban [21,22] from a US payer/Medicare perspective.…”
Section: Discussionmentioning
confidence: 97%
“…In fact, in several studies, dabigatran etexilate was found to be cost effective among different countries and settings [61,[66][67][68][69]. Similarly, two analyses recently established the cost effectiveness of rivaroxaban [21,22] from a US payer/Medicare perspective.…”
Section: Discussionmentioning
confidence: 97%
“…Current guidelines for stroke prevention published jointly by the American College of Cardiology Foundation/American Heart Association/Heart Rhythm Society as well as those from the American College of Chest Physicians [44], [45] recommend the oral direct thrombin inhibitor, dabigatran, as an alternative to warfarin for patients who are at moderate to high risk for stroke. [3] Dabigatran has been found to be a cost – effective alternative in this population in a large majority of published economic models [12], [46][50]. At present, only a single published Markov model has evaluated the oral factor Xa inhibitor, rivaroxaban's, cost-effectiveness compared to warfarin in this setting [51].…”
Section: Discussionmentioning
confidence: 99%
“…We excluded patients on a forced INR schedule from the study and, logically, determining the number of INR tests in a 6-month period is not applicable for patients who are managed using a fixed INR testing schedule. Although cost-effectiveness analyses have shown that NOACs are cost-effective from a societal perspective [18][19][20][21], national drug plans, Medicare and other drugreimbursing organizations cannot realistically absorb the difference in price between a tablet of VKA (from 0.25 to 0.50 CAN$ per day) and the NOACs (from 2.85 to 4.20 CAN$ per day). However, the identification of patients with poor anticoagulation control on VKAs may lead to more effective and well tolerated treatment with NOACs that may actually be associated with a cost savings, realized through a reduction in morbidity and hospitalizations and an increase in quality of life.…”
Section: Discussionmentioning
confidence: 99%